Pentingnya Pelayanan Bimbingan dan Konseling Pada Pendidikan Anak Usia Dini (PAUD) - Amanah, Siti; Riyanto, Dedi; Rizqullah, Dhilal (Universitas Mathla'ul Anwar Banten, 2023)
Implementation of guidance and counseling services at Early Childhood Education Institutions is carried out to help children so that children can develop optimally and prepare Early Childhood Children to undergo the next stage of education, namely basic education. Guidance and counseling services in early childhood education are considered important because they are in line with the goals of PAUD services stipulated in the Minister of Education and Culture Regulation Number 18 of 2018 concerning Early Childhood Education Services which aim to serve Early Childhood Education and the Sustainable Development Goals or SDGs so that children have access to quality early childhood development and care, preschool education as preparation for basic education by implementing student-centred guidance and counseling services by adjusting the background and support from teachers, parents, and related parties. This article examines the importance of implementing guidance and counseling in Early Childhood Education to see how it needs to be implemented.